PERANCANGAN ALAT MONITORING KONDISI LINGKUNGAN DAN PREDIKSI CUACA BERTENAGA SURYA BERBASIS MIKROKONTROLER MENGGUNAKAN METODE FUZZY LOGIC: Indonesia - Athalarvin Nabilfathin Arvin; Rusindiyanto (Universitas Majalengka, 2022)
Indonesia is an agricultural country where agriculture plays an important role in the overall national economy. This happens because agricultural and plantation products are influenced by environmental factors and supervision. This study aims to design a tool for monitoring environmental conditions and weather predictions with solar power as well as developing an IoT that connects weather monitoring and prediction tools with smartphones. So it is hoped that from the results of this study, a solar-powered monitoring and weather prediction tool can be made that can send the latest information related to environmental conditions to smartphones owned by farmers and other users. This research is using experimental method. Data processing carried out is fuzzification and defuzzification. Fuzzi inference according to Sugeno which is represented in the form of IF-THEN, where the system output is a constant or a linear equation. The results of this study found that the design of the environmental condition monitoring tool was successful in displaying data with an accuracy rate of 0.34% for the temperature variable, 0.19% for the humidity variable, and 0.83% for the irradiation variable, then the solar panel was able to charge power bank to generate sufficient electrical power for the device to operate continuously well in conditions such as in a research environment, as well as the IoT software developed to successfully display all data captured by the monitoring tool properly